Pewartaan Iman di Media Sosial dan Pengaruhnya terhadap OMK Pasca Pandemi - Yohanes Is Nugroho; Antonius Denny Firmanto (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2022)
The coronavirus pandemic and advances in communication technology are new realities that the Church today has to face. These changes greatly affected the task of preaching and the effort to pass on the faith and values ​​of the gospel to young people. This paper aims to overview today's Catholic youth and their reality of contributing to the Church's evangelization work to young people. The research was conducted using a qualitative approach with questionnaires and descriptive analysis methods. The author finds that proclaiming the faith to young people through youth community activities such as Orang Muda Katolik and social media is very contextual to the lives of young people. Through youth activities, faith is conveyed in a way that follows the teachings of the Church and is contextual to the active lives of young people. The Church also strongly supports the proclamation of the faith through media as social media as a new way of evangelization. Social media is part of the lives of today's Catholic youth. Religious people also contribute to the spread of Christian values ​​through social media for young people.